Implementasi Manajemen Risiko Likuiditas Syariah untuk Menjaga Stabilitas Dana Pihak Ketiga (DPK) - Gusti Oka Widana; Achmad Nazhorie (Jurnal Ilmiah Ekonomi Islam, 2025)
The continuity of Islamic banking activities (BUS) is largely determined by the success of the collection of Third Party Funds (DPK) (Fitriani & Azizoma, 2022; Parenrengi & Hendratni, 2018; Utami, 2023). In addition to indicating the level of public trust (Jyana & Affandi, 2019; Wati & Fasa, 2024), deposits are a vital factor in boosting bank profitability (ROA) (Parenrengi & Hendratni, 2018; Saputri & Nursamsiyah, 2025; Sriyono, Dewi, Hidayati, & Maulida, 2023). However, banking institutions face the threat of Liquidity Risk which is very critical (Nelly, Siregar, & Sugianto, 2022). This risk arises due to the bank's inability to pay off all its financial obligations that have matured (Handayani, 2017; Nelly, Siregar, & Sugianto, 2022), thus being considered a serious threat that triggers bankruptcy ("bank killer") (Sultoni & Mardiana, 2021; Nelly, Siregar, & Sugianto, 2022). Therefore, the effective implementation of Sharia Liquidity Risk Management (MRLS) is absolutely necessary to ensure bank resilience (Adiyes Putra, Agus, & Saparuddin, 2023; Watts & Phase, 2024; Sultoni & Mardiana, 2021). However, there is a research gap (Capriani & Dana, 2016; Ichwan & Nafik, 2016; Sultoni & Mardiana, 2021) related to the correlation between deposits and liquidity levels. This inconsistency is reflected in findings that show insignificant results (Fitriani & Danisworo, 2020; Muslim & Mugiyati, 2025) and findings that indicate significant influence (Fitriani & Azizoma, 2022; Nursupian, 2025). Therefore, this study aims to, Describe and analyze the process of implementing MRLS (identification, measurement, monitoring, and control), Identify sharia-compliant instruments and strategies that are predominantly used, Explore the effectiveness of MRLS in maintaining deposit stability.